The nutrient content, growth, yield, and yield attribute traits of rice (Oryza sativa L.) genotypes as influenced by organic fertilizer in Malaysia - Anisuzzaman, Mohammad; Rafii, Mohd Yusop; Ramlee, Shairul Izan; Md Jaafar, Noraini; Ikbal, Mohammad Ferdous; Haque, Md Azadul (Multidisciplinary Digital Publishing Institute, 2022)
One of the most important challenges to continuously maximizing crop production on limited areas of agricultural land is maintaining or enhancing soil fertility. Organic fertilizer application is needed to replace nutrients recovered by crops from the fields in order to restore the crop production potential of the soil. The utilization of chicken manure as an organic fertilizer is essential in improving soil productivity and cop production. In Malaysia, demand for rice as a food source is rising in tandem with population growth, while paddy rice production capacity is becoming increasingly constrained. Field experiments were carried out in Sungai besar, Kuala Selangor, Malaysia during the two planting seasons in 2020 to evaluate the effects of different levels of organic fertilizer on the growth and yield of rice genotypes. A split plot layout in a randomized complete block design with three replicates was used. The twelve rice genotypes were in the main plots. The sub-plots were treatments. The experiment comprised 4 treatments, viz., T1 = 100% NPK (N150P60K60), T2 = Chicken manure @ 5 t ha−1, T3 = Chicken manure @ 7 t ha−1, and T4 = Chicken manure @ 10 t ha−1. The study indicated that different levels of chicken manure and NPK fertilizer showed significant effects on growth, yield, and yield contributing characters of all the rice genotypes. Results showed that application of chicken manure 10 t ha-1 was the best in producing growth and yield contributing characters, grain and straw yields, and also nutrient (N, P, and K) contents in grain and straw. The maximum number of panicles (422.56 panicles m−1), the maximum number of filled grains (224.49 grains panicle−1), and the maximum grain yield (8.02 t ha−1) and straw yield (9.88 t ha−1) were recorded from T4 treatment at the rice genotype BRRI dhan75. Although the highest biological yield was recorded from T4 treatment, a statistically similar result was found for T3 treatment. The highest harvest index was also recorded for T4 treatment. Therefore, rice genotype BRRI dhan75 can be recommended under chicken manure @ 10 t ha−1 for rice production in Malaysia.